2022
DOI: 10.1162/jocn_a_01864
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Temporal Community Structure in Hippocampus and Precuneus Predict Inductive Reasoning Decisions

Abstract: Our understanding of the world is shaped by inferences about underlying structure. For example, at the gym, you might notice that the same people tend to arrive around the same time and infer that they are friends that work out together. Consistent with this idea, after participants are presented with a temporal sequence of objects that follows an underlying community structure, they are biased to infer that objects from the same community share the same properties. Here, we used fMRI to measure neural represe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 101 publications
3
24
0
Order By: Relevance
“…Reasoning the hidden relational structure from outside events is a crucial ability we human beings possess to help predict the future and make inferences (Balaguer et al, 2016; Garvert et al, 2021; Pudhiyidath et al, 2021). Here we demonstrate the behaviorally-related neural representations of two key aspects of relational knowledge – lower-order transition probability and higher-order community structure, which occur around 840 msec after image onset, before making a response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reasoning the hidden relational structure from outside events is a crucial ability we human beings possess to help predict the future and make inferences (Balaguer et al, 2016; Garvert et al, 2021; Pudhiyidath et al, 2021). Here we demonstrate the behaviorally-related neural representations of two key aspects of relational knowledge – lower-order transition probability and higher-order community structure, which occur around 840 msec after image onset, before making a response.…”
Section: Discussionmentioning
confidence: 99%
“…This neural signature occurs around 840 msec after image onset, before subject make responses, and could well explain the subsequent behavioral performance (i.e., RTs). Previous fMRI studies have revealed multiple brain regions, such as the hippocampus, inferior prefrontal gyrus (IFG), insula, anterior temporal lobe (ATL) in representing the network-based temporal relationship (Pudhiyidath et al, 2021; Schapiro et al, 2013; Schapiro et al, 2016). Thus, the observed neural signature might arise from collective contributions from many brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations